2015
DOI: 10.2139/ssrn.2611887
|View full text |Cite
|
Sign up to set email alerts
|

Research Productivity in Management Schools of India: A Directional Benefit-of-Doubt Model Analysis

Abstract: Given the growing emphasis on research productivity in management schools in India, the present authors developed a composite indicator (CI) of research productivity, using the directional benefit-of-doubt (D-BOD) model, which can serve as a valuable index of research productivity in India. Specifically, we examined overall research productivity of the schools and the faculty members during the 1968-2014 and 2004-2014 periods in a manner never done before. There are four key findings. First, the relative wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In specific environments, some scholars challenge publication in international journals (see Sahoo et al (2015) for a discussion). They consider them biased against developing countries' problems, issues, data, and researchers.…”
Section: Conceptual Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In specific environments, some scholars challenge publication in international journals (see Sahoo et al (2015) for a discussion). They consider them biased against developing countries' problems, issues, data, and researchers.…”
Section: Conceptual Discussionmentioning
confidence: 99%
“…The discussion concerns the legitimacy of using indexed international publishing as the main output of the scientific community. Nevertheless, the growing tendency to collaborate through international co-authorship is an important counterargument against the isolation argument ("a native writes for natives") (Sahoo et al, 2015). The use of publications as an output measure of research has the disadvantage of being retrospective.…”
Section: Conceptual Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pressure leads to more and better-quality publications. On the other hand, it was found out that in India, both public and private schools were the same in research productivity with journal tier, total citations, impact factor, author h-index, number of papers and journal h-index as the main factors for research productivity (Sahoo et al, 2015). Also, the same study found that faculty members who had doctoral degrees from foreign schools were more productive.…”
Section: Research Culturementioning
confidence: 91%